2022
DOI: 10.3390/plants11192511
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of the Zinc Finger Protein Gene Subfamilies under Drought Stress in Triticum aestivum

Abstract: The zinc finger protein (ZFP) family is one of plants’ most diverse family of transcription factors. These proteins with finger-like structural domains have been shown to play a critical role in plant responses to abiotic stresses such as drought. This study aimed to systematically characterize Triticum aestivum ZFPs (TaZFPs) and understand their roles under drought stress. A total of 9 TaC2H2, 38 TaC3HC4, 79 TaCCCH, and 143 TaPHD were identified, which were divided into 4, 7, 12, and 14 distinct subgroups bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…The C2H2-zinc finger protein family plays several important roles in plant growth and development, and has been extensively studied in various species including Arabidopsis thaliana Frontiers in Genetics frontiersin.org (Englbrecht et al, 2004), Zea mays (Wei et al, 2016), Triticum aestivum (Li et al, 2021;Wu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The C2H2-zinc finger protein family plays several important roles in plant growth and development, and has been extensively studied in various species including Arabidopsis thaliana Frontiers in Genetics frontiersin.org (Englbrecht et al, 2004), Zea mays (Wei et al, 2016), Triticum aestivum (Li et al, 2021;Wu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…C2H2-ZFPs are one of the most important transcription factor families in higher plants, playing a crucial role in plant development and stress resistance ( Han et al., 2021 ; Liu et al., 2022a ; Liu et al., 2022b ). Previous reports have shown that they can play important roles in Arabidopsis thaliana , wheat, grapevine, sorghum, and cotton ( Englbrecht et al., 2004 ; Salih et al., 2019 ; Arrey-Salas et al., 2021 ; Cui et al., 2022 ; Wu et al., 2022 ). However, there are few reports on the C2H2-ZFPs in sweetpotato.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the values of Ks (synonymous) and Ka (nonsynonymous) as well as the ratio of Ka/Ks. Ka/Ks < 1, Ka/Ks = 1, and Ka/Ks > 1 generally indicate negative, neutral, and positive selection, respectively [ 76 , 77 , 78 ].…”
Section: Methodsmentioning
confidence: 99%